2021
DOI: 10.3390/ijms22105389
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotection of the Perinatal Brain by Early Information of Cerebral Oxygenation and Perfusion Patterns

Abstract: Abnormal patterns of cerebral perfusion/oxygenation are associated with neuronal damage. In preterm neonates, hypoxemia, hypo-/hypercapnia and lack of cerebral autoregulation are related to peri-intraventricular hemorrhages and white matter injury. Reperfusion damage after perinatal hypoxic ischemia in term neonates seems related with cerebral hyperoxygenation. Since biological tissue is transparent for near infrared (NIR) light, NIR-spectroscopy (NIRS) is a noninvasive bedside tool to monitor brain oxygenatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 106 publications
0
9
0
Order By: Relevance
“…Primary rat cerebral cortical neurons were isolated from a timed‐pregnancy embryonic day 14–16 Sprague Dawley rat pups, as previously described (Costa et al., 2021 ). Briefly, pregnant rats were anesthetized with 3% isoflurane and then pups were taken out of the embryo and euthanized by excessive injection of pentobarbital sodium (150 mg/kg).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Primary rat cerebral cortical neurons were isolated from a timed‐pregnancy embryonic day 14–16 Sprague Dawley rat pups, as previously described (Costa et al., 2021 ). Briefly, pregnant rats were anesthetized with 3% isoflurane and then pups were taken out of the embryo and euthanized by excessive injection of pentobarbital sodium (150 mg/kg).…”
Section: Methodsmentioning
confidence: 99%
“…Cerebral ischemia‐reperfusion (I/R) injury is a pathophysiological cascade that can lead to brain injury and tissue deterioration, which compromises the beneficial effect of recanalization (Costa et al., 2021 ). Ischemic tissue reperfusion can cause increased reactive oxygen species (ROS), inflammation, necrosis and apoptosis, which aggravate the injury and worsen the prognosis of patients (Guan et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Comparative analysis revealed that rSO 2 monitoring can provide real-time trend information regarding cerebral oxygenation under aortic occlusion. rSO 2 monitoring is highly important for understanding the health conditions of infants and young children [ 80 ]. Early treatment should be administered if cerebral ischemia and hypoxia are discovered so as to prevent further aggravation and unnecessary burden.…”
Section: Cerebral Blood Oxygen Saturation Monitoring Methodsmentioning
confidence: 99%
“…[ 102 ] To date, hypothermia to 33.5°C for 72 h is the only established treatment for reducing reperfusion injury after birth asphyxia. [ 103 ]…”
Section: Changes Of Ca During Hypothermiamentioning
confidence: 99%